"Anything Is Better than Nothing!" Inservice Teacher Preparation for Teaching Students with Disabilities. Issue 3 (June 2020) - Grimsby, Rachel
The purpose of this instrumental case study was to examine three elementary music teacher's perceptions of preparation to work with students with disabilities. Research questions included the following: How do elementary general music teachers define preparedness for working with students with disabilities? What challenges do elementary general music teachers face in their work with students with disabilities? What resources do general music teachers identify as helpful? Based on major themes that emerged from the analysis, I concluded general music teachers need more preservice preparation and ongoing professional development focused on students with disabilities, more time to collaborate with special education professionals, more consistent communications and recommendations about how to work with students who have disabilities, and access to assistive technologies.